2020
DOI: 10.5267/j.msl.2019.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Leadership, quality of worklife, job satisfaction and organizational citizenship behavior in PT. Pertamina

Abstract: Organizational citizenship behavior (OCB) is a form of positive, constructive and meaningful social behavior that helps the tasks given by the leadership become lighter if there are workers with high OCB and that the consequences will increase productivity and success which can be seen as a factor that contributes to the work of the company. This study aims to examine the leadership and quality of worklife on organizational citizenship behavior mediated by job satisfaction at PT. Pertamina (Persero). The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…The issue of job satisfaction has been the center of attention among academics, researchers, and practitioners because its existence is very important for organizations, especially educational organizations, including school organizations at the level of early childhood education. As shown by several studies in various organizations, industries, and country that job satisfaction proven significantly influences organizational commitment (Talasaz, Saadoldin, & Shakeri, 2017;Ćulibrk et al 2018;Yao, Qiu, & Wei, 2019), organizational citizenship behavior (Motalebi & Marşap, 2020;Moestain, Hamidah, & Kadir, 2020;Ramadhan, Saudi, & Yenni, 2018), productivity (Embuldeniya, 2017), and performance (Oravee, Zayum, & Kokona, 2018;Abdulkhaliq, & Mohammadali, 2019). Job satisfaction is a pleasurable emotional state resulting from the appraisal of one's job or job experiences, it represents how you feel about your job and what you think about your job (Colquitt, Lepine, & Wesson, 2015;Noe et al, 2015;McShane, & Von Glinow, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of job satisfaction has been the center of attention among academics, researchers, and practitioners because its existence is very important for organizations, especially educational organizations, including school organizations at the level of early childhood education. As shown by several studies in various organizations, industries, and country that job satisfaction proven significantly influences organizational commitment (Talasaz, Saadoldin, & Shakeri, 2017;Ćulibrk et al 2018;Yao, Qiu, & Wei, 2019), organizational citizenship behavior (Motalebi & Marşap, 2020;Moestain, Hamidah, & Kadir, 2020;Ramadhan, Saudi, & Yenni, 2018), productivity (Embuldeniya, 2017), and performance (Oravee, Zayum, & Kokona, 2018;Abdulkhaliq, & Mohammadali, 2019). Job satisfaction is a pleasurable emotional state resulting from the appraisal of one's job or job experiences, it represents how you feel about your job and what you think about your job (Colquitt, Lepine, & Wesson, 2015;Noe et al, 2015;McShane, & Von Glinow, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the dependent variable, namely organizational citizenship behavior refers to (Smith, Organ, & Near, 1983) and (Haerani, Sumardi, Hakim, Hartini, & Putra, 2020) which consists of 5 indicators. Furthermore, the first independent variable, namely the quality of work-life, refers to previous research (Pio & Lengkong, 2020) and (Moestain et al, 2020), which consists of 5 indicators. Then the second independent variable, namely leader-member exchange, refers to previous research (Graen & Scandura, 1987) and (Li et al, 2020) which consists of 4 indicators.…”
Section:  Methodsmentioning
confidence: 99%
“…Employee compensation, capacity to engage in the organization, work safety, job design, and the quality of inter-organizational contact all contribute to the quality of work-life, according to (Mayasari, 2019). Research result by (Hastuti1 & Wibowo, 2021) and (Moestain, Hamidah, & Kadir, 2020) revealed a relationship between the quality of work-life with OCB.…”
Section:  Introductionmentioning
confidence: 94%
“…Produktivitas PNS sendiri dapat dilihat apakah sudah sesuai dengan tugas pokok dan fungsi PNS dalam unit kerja masing-masing. Pengukuran produktivitas PNS sudah diatur dalam peraturan Menpan RB No 1 tahun 2020 tentang analisis beban kerja [12].…”
Section: 5unclassified